Business history and European integration: How EEC competition policy affected companies' strategies. Issue 5 (3rd July 2020) - Rollings, Neil; Warlouzet, Laurent
Abstract: This introduction to the special issue on business responses to European competition policy considers the development of research in the field of European competition policy. It is argued that existing analyses have concentrated on the development of policy over time and that we know surprisingly little about the response of business to the demands of competition policy. This is important because it is apparent that ever stricter legal provision has not removed the problem and where there appears to be a considerable degree of recidivism. The aim of the special issue is to begin to address these issues by examining the response of different companies and sectors to the existence of EEC/EU competition policy.